Gastropreneurship Katupat Kandangan as a Tourism Attraction in the South Hulu Sungai in South Kalimantan - Hendri Gigih Saputro; Lastiani Warih Wulandari (Gastronomy Tourism Journal, 2023)
This study aims to find out whether the traditional Katupat Kandangan food has a gastronomic component, How is the effort to preserve traditional Katupat Kandangan food through the Miss Helix method in Hulu Sungai Selatan Regency, South Kalimantan Province, and How is the development of traditional Katupat Kandangan food as a Gastronomic Tourism Attraction in Hulu Sungai Regency South Kalimantan Province.This study uses a type of qualitative research with data collection techniques using observation, interviews, and documentation. The results show that Katupat Kandangan has the potential to be used as a gastronomic tour because the valveat Kandangan includes all the elements of the 9 gastronomic components. Preservation Efforts in the Miss Helix method states that in order to preserve Katupat Kandangan it is necessary to implement programs that support cultural progress. The development of a gastronomic tourism attraction in Kandangan, Hulu Sungai Selatan Regency, has not been given enough attention by the local government and entrepreneurs to make it a gastronomic city.